Byzantine Studies in dissertations produced by Ukrainian scholars, 2012–2022 (Historical Sciences) - Domanovska, Maryna; Domanovskyi, Andriy (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2022)
The article reviews the dissertations on Byzantine studies, which have been defended in Ukraine over the past decade in historical specialties within the field of “historical sciences”. Byzantine studies in Ukraine, as in previous periods, continue to develop in institutional centers, among which are V. N. Karazin Kharkiv National University, M. S. Grushevsky Institute of Ukrainian Archeography and Source Studies NASU, Ivan Franko National University of Lviv, National Reserve “Sophia of Kyiv”, I. I. Mechnikov Odessa National University etc. The range of dissertations of an interdisciplinary nature is expanding, in particular, historical, theological, historical and philosophical topics are gaining popularity, and art criticism and musicology are becoming popular. The review identifies the reasons for the reduction in the number of defended dissertations in Byzantine studies during 2012–2022 in the comparison to previous periods. However, the studies presented in the review are original, based on the latest methods and achievements of world science, and they also determine further vectors of the development of Ukrainian Byzantine studies in the near future.